2013
DOI: 10.3126/jcmc.v3i2.8441
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Profile of Chronic Kidney Disease (CKD) Patients in Various Age and Gender Group Subjects Visiting Kist Medical College & Teaching Hospital, Kathmandu

Abstract: Nowadays it is observed that the chronic kidney disease (CKD) is a growing health problem worldwide and the most com­mon illness associated with this is hypertension (HTN) and diabetes mellitus (DM). This study tries to find out illness associ­ated with CKD and assess the renal parameters according to age and sex group. This is a cross sectional descriptive study. Diagnosed cases of Chronic Kidney Disease patients visiting at KIST Medical College from September to November 2011 are included in this study. SPSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
3
3
2
Order By: Relevance
“…5 Similar etiological proportions have been reported by various studies in different tertiary centres of Nepal. 6 , 7 In contrast to ours, studies from India report diabetes as the most common underlying comorbidity followed by hypertension. 10 , 11 …”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…5 Similar etiological proportions have been reported by various studies in different tertiary centres of Nepal. 6 , 7 In contrast to ours, studies from India report diabetes as the most common underlying comorbidity followed by hypertension. 10 , 11 …”
Section: Discussioncontrasting
confidence: 93%
“…4 Various institutional studies of Nepal have shown hypertension and diabetes as the major causes of CKD with a prevalence of 24.5% and 5.8% respectively. [5][6][7][8] The more widespread efforts at prevention, early detection, evaluation, and management of CKD and antecedent conditions could prevent complications of decreased kidney function.…”
Section: Introductionmentioning
confidence: 99%
“…The present study was conducted in order to identify biochemical changes and prolactin secretion in CKD patients in comparison with controls, with emphasis on differences which may have had an impact on diagnostic or therapeutic approaches. Several studies correspond that chronic kidney disease typically increases with age 8,12 which supports this study. Older adults are, therefore, at increased risk for chronic kidney disease.…”
Section: Discussionsupporting
confidence: 90%
“…CKD can be detected via simple biochemical tests. 8 These tests include a creatinine-based estimate of the glomerular filtration rate (GFR), serum creatinine 2 , RBC, urea etc. 9 CKD is characterized by elevation of serum prolactin levels.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding comorbidity, the majority had hypertension followed by diabetes mellitus which is relevant with previous findings. 23,24 This is common for patients having vascular problems.…”
Section: Discussion Participants' Sociodemographic Characteristicsmentioning
confidence: 99%